The Relationship Between the Family Communication and Talking Early Children at the Pisang Village Kinali Districts Pasaman Barat - Annisa Miftahus Shaumi; Ismaniar Ismaniar (Universitas Negeri Padang, 2020)
This research was motivated by the low speaking ability of early childhood in Pisang Village, Kinali District, Pasaman Regency. It is suspected that one of the reasons is because the communication applied in the family is not quite right. This study aims to: 1) describe the communication that occurs in the family; 2) describe early childhood speech skills; and 3) looking at the relationship between communication within the family and the speaking ability of aged children in Pisang Village, Kinali District, West Pasaman Regency. This research is correlational quantitative research. The population in this study were 26 housewives who had children aged 4-5 years. The sample amounted to 19 people with sampling using a simple random sampling technique. The data collection technique used a questionnaire and a check for the observation of the development of speech in early childhood. The data obtained were analyzed using descriptive analysis and the correlation formula of the Sperman Rho correlation. The results of this study indicate: 1) the communication that occurs within the family in Pisang Village is in the wrong category; 2) the speaking ability of early childhood in Kampung Pisang is still low; and 3) there is a significant relationship between communication within the family and the speaking ability of early childhood in Pisang Village, Kinali District, West Pasaman Regency. Research suggestions are: 1) it is hoped that the family can implement good, dynamic, intensive, and harmonious communication with children, to improve their speaking ability in children; and 2) it is hoped that further researchers will be able to examine other variables that affect the development of children's self-speech abilitiesKeywords: communication, speech application, early childhood, family education